Czy idee nacjonalistyczne zakwestionują społeczeństwo liberalno-demokratyczne? Rozważania o przyszłości narodu w świecie diaspory i bezdomności - Grzybowski, Jacek (Civitas. Studia z filozofii polityki, 2012)
The author attempts to answer, by describing the phenomena involved, the question as to whether nationalist (national) ideals constitute a real threat to liberal democracy and whether, despite the popularity of nationalism, it is possible to create a post national, multicultural and cosmopolitically liberal world? Disputes around the concept of nationalism are set out, as exemplified by the views of Jacek Woroniecki and Jozef Maria Bocheński.